Insulitis in transgenic mice expressing tumor necrosis factor beta (lymphotoxin) in the pancreas. - Picarella, D E (1992)
Tumor necrosis factor beta (TNF-beta) (lymphotoxin) may play an important role in the immune response and pathologic inflammatory diseases. Insulitis is an important early step in the development of insulin-dependent diabetes mellitus. To understand better the role of TNF-beta in the regulation of inflammation and type 1 diabetes, we produced transgenic mice in which the murine TNF-beta gene was regulated by the rat insulin II promoter. The transgene was expressed in the pancreas, kidney, and skin of transgenic mice. The expression of TNF-beta in the pancreas of transgenic mice resulted in a leukocytic inflammatory infiltrate consisting primarily of B220+ IgM+ B cells and CD4+ and CD8+ T cells. The insulitis is reminiscent of the early stages of diabetes, though the mice did not progress to diabetes.